1999
DOI: 10.1007/s11746-999-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐phase catalytic oxidation of unsaturated fatty acids

Abstract: Liquid‐phase catalytic oxidation of oleic acid with hydrogen peroxide in the presence of various transition metal/metal oxide catalysts was studied in a batch autoclave reactor. Azelaic and pelargonic acids are the major reaction products. Tungsten and tantalum and their oxides in supported and unsupported forms were used as catalysts. Alumina pellets and Kieselguhr powder were used as supports for the catalysts. Tungsten, tantalum, molybdenum, zirconium, and niobium were also examined as catalysts. Tertiary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…Under the conditions described above and using HY340, HY340-900, GO e UP as the catalysts, studies carried out with methyl oleate did not provide a significant number of products (<1%) ( Figure S4) [49].…”
Section: Oxidation Reaction Of Linoleic Acid Methyl Ester Catalyzed Bmentioning
confidence: 97%
See 1 more Smart Citation
“…Under the conditions described above and using HY340, HY340-900, GO e UP as the catalysts, studies carried out with methyl oleate did not provide a significant number of products (<1%) ( Figure S4) [49].…”
Section: Oxidation Reaction Of Linoleic Acid Methyl Ester Catalyzed Bmentioning
confidence: 97%
“…The catalytic systems based on niobium oxide are reasonably selective in oxidative processes [58], such as the selective epoxidation of allylic alcohols [59], the opening of epoxy rings [60], the selective oxidation of geraniol [61], the cyclohexene epoxidation [62], the selective oxidation of terpenes [63,64] and the oxidation of unsaturated fatty acid derivatives [49,65].…”
Section: Introductionmentioning
confidence: 99%
“…Tungstic oxide supported on silica was the most suitable catalyst for the oxidation of OA with 85% of OA conversion and a high selectivity for AA within 60 min [71]. Rü sch et al [56] found a moderate yield of 52% MMA using Re 2 O 7 /H 2 O 2 .…”
Section: Direct Cleavage Of Monoenic Fatty Acids and Estersmentioning
confidence: 99%
“…Efforts are ongoing to utilize the abundantly available fatty oils and oil-based products for production of mono and dicarboxylic acids which in turn find major potential application as better substitutes for petroleum-based products [3,4]. Among these dicarboxylic acids is azelaic acid, which been used in industry as an intermediate for many applications, for example production of polyamides, polyesters, pharmaceuticals, plasticizers, and lubricants or hydraulic fluids [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated fatty acids are subjected to a variety of reactions with several compounds to form a wide range of products. These reactions may involve either the carboxyl group or the carbon-carbon double bond in an unsaturated fatty acid [3,8].The oxidation of unsaturated fatty acids results in partial or complete cleavage of the carbon-carbon double bond [4,11]. Mono and dicarboxylic acids are the main products of the complete oxidation of unsaturated fatty acids [3][4][5].…”
Section: Introductionmentioning
confidence: 99%